Reflexiones sobre la evaluación del logro de habilidades de estadística y probabilidad en la educación secundaria costarricense - Vargas Gamboa, José D. (2019)
One of the challenges to implementing a new program of studies is how to carry out the evaluation of learning. The purpose of this article is to disseminate a proposal designed in the framework of a Final Work of Graduation, which allows the evaluation of the achievement of skills in Statistics and Probability in eighth year of secondary education. Firstly, the inquiry was conducted theoretically to enable us to lay a basis for the proposal, then interviews and observations of class were conducted, to finally design criteria and indicators for the evaluation.